Freshwater feeding by adult chum salmon Oncorhynchus keta in the Mackenzie River, Northwest Territories - Dunmall, Karen M.; Wight, Kevin; McNicholl, Darcy G.; Tierney, Keith (Frontiers in Ecology and Evolution, 2026)
As distributional shifts of marine species into the Arctic become more frequent, these range-expanding individuals may exhibit unique traits that facilitate survival and establishment in new places. In the western Canadian Arctic, increasing incidental harvest of range-expanding Pacific salmon Oncorhynchus spp. is monitored in a collaborative effort with harvesters, Indigenous leadership, and Fisheries and Oceans Canada. As harvesters have observed both feeding behavior and prey in these salmon, it is important to investigate the hypothesis that adult salmon cease feeding in the Mackenzie River, Northwest Territories. Here, we focused on adult chum salmon Oncorhynchus keta harvested during 2017 and 2019 to explore incidences of freshwater feeding in the Delta, Mainstem, and in Great Bear and Great Slave lakes. Stomach content analyses of 150 chum salmon revealed that there were nearly equal numbers of chum with stomach contents vs. empty stomachs (70 vs. 80). When there were contents, stomach fullness remained low (fullness index range: 0.00071%–0.71%) but was the highest in the Delta. Identifiable freshwater prey was present in three chum salmon (2%). Foraging on freshwater fish was only recorded in Great Slave Lake, where two chum salmon each ate one forage fish (Coregonus spp.). Foraging on insects was only recorded in Great Bear Lake, where one chum salmon ate two corixids. Fourteen additional chum salmon stomachs (9.3%) contained prey remnants. Chum salmon stomach contents in all areas included plant materials, which were more prevalent in the Mainstem. Stomachs in all areas also included synthetic fibers, more of which were found in 2017 than in 2019. Although rare and likely opportunistic, the clearest evidence of recent feeding was in chum salmon that swam the furthest upstream. This deviation from the established life-history trait associated with a cessation of feeding in adult Pacific salmon in fresh water represents variation that may be important for these range-edge chum salmon, especially considering the substantial migration distance associated with accessing and then ascending the Mackenzie River.